Unlocking the Untapped Potential of Endothelial Kinase and Phosphatase Involvement in Sepsis for Drug Treatment Design - Luxen, Matthijs; van Meurs, Matijs; Molema, Grietje (Frontiers in Immunology, 2022)
Sepsis is a devastating clinical condition that can lead to multiple organ failure and death. Despite advancements in our understanding of molecular mechanisms underlying sepsis and sepsis-associated multiple organ failure, no effective therapeutic treatment to directly counteract it has yet been established. The endothelium is considered to play an important role in sepsis. This review highlights a number of signal transduction pathways involved in endothelial inflammatory activation and dysregulated endothelial barrier function in response to sepsis conditions. Within these pathways – NF-κB, Rac1/RhoA GTPases, AP-1, APC/S1P, Angpt/Tie2, and VEGF/VEGFR2 – we focus on the role of kinases and phosphatases as potential druggable targets for therapeutic intervention. Animal studies and clinical trials that have been conducted for this purpose are discussed, highlighting reasons why they might not have resulted in the expected outcomes, and which lessons can be learned from this. Lastly, opportunities and challenges that sepsis and sepsis-associated multiple organ failure research are currently facing are presented, including recommendations on improved experimental design to increase the translational power of preclinical research to the clinic.